2018
DOI: 10.1073/pnas.1800077115
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic action potential clamp predicts functional separation in mild familial and severe de novo forms of SCN2A epilepsy

Abstract: De novo variants in developmental and epileptic encephalopathy (DEE) show distinctive genotype-phenotype correlations. The two most recurrent variants in DEE, R1882Q and R853Q, are associated with different ages and seizure types at onset. R1882Q presents on day 1 of life with focal seizures, while infantile spasms is the dominant seizure type seen in R853Q cases, presenting at a median age of 8 months. Voltage clamp, which characterizes the functional properties of ion channels, predicted gain-of-function for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
135
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(144 citation statements)
references
References 38 publications
8
135
1
Order By: Relevance
“…Contributing to the different ages at onset and clinical symptoms may be the two different developmental expression patterns of Na V 1.2 channels in myelinated and unmyelinated nerve fibers . Recent work showed that early infantile epilepsy patients carrying SCN2A GoF missense variants responded well to SCBs, compared to late onset patients carrying LoF variants . Thus, taken together, the association between SCN2A and early seizure onset can be mostly explained by the early developmental expression of SCN2A and elevated channel function due to GoF variants and duplications.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Contributing to the different ages at onset and clinical symptoms may be the two different developmental expression patterns of Na V 1.2 channels in myelinated and unmyelinated nerve fibers . Recent work showed that early infantile epilepsy patients carrying SCN2A GoF missense variants responded well to SCBs, compared to late onset patients carrying LoF variants . Thus, taken together, the association between SCN2A and early seizure onset can be mostly explained by the early developmental expression of SCN2A and elevated channel function due to GoF variants and duplications.…”
Section: Discussionmentioning
confidence: 99%
“…Among SCN2A variant carriers, the responsiveness to medication appears to be more complex and directly linked to variant function. Those with early onset seizures (<3 months) due to GoF effects appear to respond well to SCBs, whereas those with later onset epilepsy and NDDs due to LoF variants often remain treatment resistant . There are only limited reports on pathogenic SCN3A variants; however, most of these present within the first days of life due to GoF effects and there is evidence to show that mutant channels may respond to SCBs .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations